Embryonal rhabdomyosarcoma of the uterine cervix in an adult female - Toyaja Jadhav; Manoj Gopal Madakshira; Sushil Garud (University of São Paulo, 2023)
Embryonal rhabdomyosarcoma (RMS) of the female genital tract is an uncommon malignancy, presenting mainly in the pediatric and adolescent populations, primarily affecting the first two decades of life. This malignancy presentation in adulthood is rare and is seldom seen. The incidence of this tumor affecting adult females is approximately 0.4 - 1%, with the common site being the vagina. This tumor infrequently involves the cervix. RMS has a poor survival rate and once diagnosed, it requires aggressive management by radical surgery accompanied by chemoradiation. We present a case of an anaplastic variant of embryonal RMS of the uterine cervix presenting as a cervical polyp in a 36-year-old female who complained of dyspareunia and post-coital bleeding.